How business environment shapes urban tourism industry development? Configuration effects based on NCA and fsQCA - Zhang, Hui; Long, Shujing (Frontiers in Psychology, 2022)
The optimization of business environment helps to create a good market ecological environment and promote industrial development. Based on the theory of institutional complexity, this study constructs the evaluation index system of China’s urban business environment, and analyzes the influencing factors by using NCA method. It is found that there is no necessary condition for a single element to constitute the high–level development of tourism industry, but improving public service, total market volume and innovation environment play universal role in promoting the high–level development of tourism industry. Using fsQCA for configuration analysis, two business environment configuration paths with high–level development of tourism industry are obtained, which shows that there is no single path to promote the development of tourism industry. In addition, the antecedent paths of high-level and low-level tourism industry development are not opposite, presenting asymmetric causal relationship. The above findings reveal the realization path of the business environment for the development of China’s urban tourism industry. Under the logic of multiple systems, cities can find the business ecological environment that best matches the development of local tourism industry.